World Food and the Canadian "Breadbasket" (Ottawa, Canada : North-South Institute, 1978)
This book is on global discrepancies among food production, food consumption and food need.
Volume IV
Includes bibliographical footnotes.
oo 12/04/2019
Loans
Keywords: Agriculture and state; Food relief; Food supply; Canada